Stimulation of vesicular stomatitis virus in vitro RNA synthesis by microtubule-associated proteins. - Hill, V M (1986)
Microtubule-associated proteins purified from bovine brains stimulated the in vitro transcription and replication reactions of vesicular stomatitis virus. The products of these reactions were intact messenger or genome-sized RNA species. A preparation from HeLa cells containing tubulin and microtubule-associated proteins also stimulated vesicular stomatitis virus transcription in vitro. This observation is in accord with previous studies, which suggested that a host cell factor was involved with the function of the vesicular stomatitis virus RNA polymerase, and others that indicated that several animal viruses displayed an association with host cell cytoskeletal elements during their replication cycles. We show evidence in this report of a host cell protein that seems to have a functional role in interacting with the virion polymerase.